(untitled) (Research, Society and Development, 2021)
Hodgkin’s lymphoma is a malignant disease, characterized by a mass wich contains lymphoid and reactive cells resulting from a clonal expansion of the hematopoietic and reticuloendothelial systems. Its incidence has a bimodal peak, with young adults and the elderly being the most affected age groups. This article seeks to analyze the outcome of deaths from this disease in Brazil, in the Northern region and in the state of Amapá, over a period of 10 years. The study presented is epidemiologically descriptive, documentary and retrospective. The data were obtained through the online atlas of cancer mortality from INCA. In Brazil, growth was observed in the first years and the numbers fluctuated in the coming years. In all regions, the age group with the highest index is adults and man predominate over women. The northern region follows the brazilian pattern, with emphasis on the states of Pará and Amazonas, which have the highest mortality rates. Amapá occupies the fifth place in the Northen region, concentrating the largest number in its capital, Macapá. The southeastern region of the country concentrates the largest number of cases, and factors such as a greater population density, greater number of people infected with HIV and the concentration of centers specialized in cancer treatment corroborate this. The number of deaths in the country is in accordance with the bimodal incidence format of the disease. Information, notification, prevention and treatment of the disease should be promoted more in Brazil, since an early diagnosis allows a better prognosis and a reduction in the number of deaths.